1989
DOI: 10.1111/j.1432-1033.1989.tb14924.x
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of DNA synthesis by microtubule disruption in quiescent rat 3Y1 cells

Abstract: Disruption of cytoplasmic microtubules by colchicine, colcemid or vinblastine induced the initiation of DNA synthesis and cell division in quiescent cultures of rat embryo fibroblast cell line, 3Y1, in the absence of growth factors. The microtubule-disruption-induced DNA synthesis was so marked that we could initiate analysis of the mechanism. Incubation of quiescent 3Y 1 cells with high concentrations of vinblastine or those of vinblastine plus colcemid, which formed large tubulin paracrystals concomitant wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Similarly, colchicine was found to promote the growth-factor-driven cell cycle traverse in animal cells (Teng et al 1977). Transient disintegration of the MT cytoskeleton was reported by several authors to be necessary for the completion of the G1/S transition and subsequent initiation of DNA synthesis in non-transformed animal cells (Vasiliev et al 1971, Crossin and Carney 1981a, Chou et al 1984 mildew interactions 149 Shinohara et al 1989). Other authors observed that depolymerization of MTs enhanced DNA synthesis in mouse fibroblasts stimulated with peptide growth factors (Friedkin et al 1979(Friedkin et al , 1980.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, colchicine was found to promote the growth-factor-driven cell cycle traverse in animal cells (Teng et al 1977). Transient disintegration of the MT cytoskeleton was reported by several authors to be necessary for the completion of the G1/S transition and subsequent initiation of DNA synthesis in non-transformed animal cells (Vasiliev et al 1971, Crossin and Carney 1981a, Chou et al 1984 mildew interactions 149 Shinohara et al 1989). Other authors observed that depolymerization of MTs enhanced DNA synthesis in mouse fibroblasts stimulated with peptide growth factors (Friedkin et al 1979(Friedkin et al , 1980.…”
Section: Discussionmentioning
confidence: 90%
“…In different experimental systems, disorganization of MTs was reported to be a sufficient trigger for mitogenic activation of some quiescent animal cells without the need for otherwise essential growth factors (Chou et al 1984, Miura et al 1987, Tsuji et al 1992. On the other hand, stabilization of MTs with taxol was found to prevent the colchicine-induced enhancement of the G1/S transition (Crossin and Carney 1981b, Chou et al 1984, Shinohara et al 1989, Tsuji et al 1992, as well as the stimulation of DNA synthesis by cytomegalovirus (Ball et al 1990). All these findings support the notion that stable MTs are important for expression of negative control over interphase progression, especially during final stages of the G1 phase, and in this way they seem to participate in execution of the crucial G1/S check-point.…”
Section: Discussionmentioning
confidence: 99%
“…The increased number of mitotic Wgures at 4-12 h suggests that although colchicine arrested cells at the metaphase stage, it did not block new cells from entering the cell cycle during this time, and possibly could have stimulated mitosis. Although colchicine is a well-known antimitotic agent, in vitro it may stimulate DNA synthesis, and the related microtubule depolymerizing agent colcemid actually promotes cell division (Shinohara et al, 1989).…”
Section: Apo Histologymentioning
confidence: 99%
“…At 10 and 20 mM, there were less abundant stress fibers present after stimulation with LPA or nocodazole, while 40 are similar and mediated by Rho-dependent actin stress fiber formation and cell contraction. The depolymerization of cellular microtubular system elucidates diverse pleiotropic effects on cells, including the assembly of prominent actin cables (Danowski, 1989;Kajstura and Bereiter-Hahn, 1993), an increase in the number and size of vinculin-containing focal adhesions (Lloyd et al, 1977), local tyrosine phosphorylation of the focal adhesion proteins FAK and paxillin (Bershadsky et al, 1996), and the stimulation of DNA synthesis (Crossin and Carney, 1981;Shinohara et al, 1989). The impairment of microtubules may block intracellular vesicular transport and affect signaling by blocking receptor internalization or recycling (Kapeller et al, 1993).…”
Section: Involvement Of Rho-dependent Contractility In Fn Bindingmentioning
confidence: 99%